KEMATANGAN KARIR MENGGUNAKAN TES MI SEBAGAI PENDUKUNG TES SDS PADA MAHASISWA UNIVERSITAS PANCASAKTI TEGAL - Budisiwi, Hastin; S., M. Arif Budiman (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2018)
The aim of study to obtain information by describing career planning through the relationship test MI (Multiple Intellegence) and test SDS (Dominance, Inducement, Submissive, Compliance) as the needs of students in choosing career planning. This research approach use descriptive qualitative. Data obtained are the results of the MI and SDS test students VII semester guidance and counseling program. The object of research is the relationship between MI and SD test results. Knowledge of a career requires students who are in the seventh semester in order to get a decent job in accordance with their competence. By knowing the results of MI test and test of SDS expected student can determine career decision as plan early from career development. The population studied is a VII semester student guidance and counseling program with. Results obtained from charging kuisoner distribution is a significant relationship relationship between MI and SDS test results based on the suitability of job choice.